2023
DOI: 10.1097/apo.0000000000000646
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Glaucoma Surgery: Latest Developments and Future Challenges

Poemen P.M. Chan,
Mark D. Larson,
Jaime E. Dickerson
et al.

Abstract: The development of minimally invasive glaucoma surgeries (MIGSs) was intended to provide safe and modestly efficacious modalities for early intervention of mild-to-moderate glaucoma, with minimal trauma and rapid recovery. They were mainly ab interno procedures that reduce intraocular pressure by facilitating the aqueous outflow by bypassing the trabecular meshwork resistance, reinforcing the uveoscleral flow via the supraciliary space, and reducing aqueous production by the ciliary body. While the cumulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 288 publications
0
1
0
Order By: Relevance
“…IOP reduction is a surrogate outcome to quantify intervention effectiveness, 45 , 46 and randomized trials have consistently shown that a 20% reduction in IOP from baseline halved the 5-year rate of glaucoma onset in the Ocular Hypertension Treatment Study, 47 and a 25% reduction significantly delayed glaucoma progression in the Early Manifest Glaucoma Trial. 48 However, in the present study, the suppression of Car2 mediated by the dual-target CRISPR system led to an average 18% reduction in normal mice and 40% reduction in glaucoma model mice, which is comparable to the decrease in IOP previously reported with disruption of aquaporin 1 24 or mutant myocilin .…”
Section: Discussionmentioning
confidence: 99%
“…IOP reduction is a surrogate outcome to quantify intervention effectiveness, 45 , 46 and randomized trials have consistently shown that a 20% reduction in IOP from baseline halved the 5-year rate of glaucoma onset in the Ocular Hypertension Treatment Study, 47 and a 25% reduction significantly delayed glaucoma progression in the Early Manifest Glaucoma Trial. 48 However, in the present study, the suppression of Car2 mediated by the dual-target CRISPR system led to an average 18% reduction in normal mice and 40% reduction in glaucoma model mice, which is comparable to the decrease in IOP previously reported with disruption of aquaporin 1 24 or mutant myocilin .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a 1-mmHg decrease in IOP leads to an estimated 10% reduction in glaucoma progression [5]. Recently, minimally invasive glaucoma surgeries have gained popularity worldwide as alternatives to conventional trabeculectomy (TLE) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%